Dar es Salaam histories from an emerging African metropolis - edited by James R. Brennan (Dar es Salaam Mkuki na Nyota Publishers, 2007)
From its modest beginnings in the mid-19th century, Dar es Salaam has grown to become one of sub-Saharan Africa's most important urban centres. A major political, economic and cultural hub, the city stood at the cutting edge of trends that transformed twentieth-century East Africa. Dar es Salaam has recently attracted the attention of a diverse, multi-disciplinary, range of scholars, making it currently one of the continent's most studied urban centres. This collection from eleven scholars from Africa, Europe, North America and Japan, draws on some of the best of this scholarship and offers a comprehensive, and accessible, survey of the city's development. The perspectives include history, musicology, ethnomusicology, culture including popular culture, land and urban economics. The opening chapter offers a comprehensive overview of the history of the city. Subsequent chapters examine Dar es Salaam's twentieth century experience through the prism of social change and the administrative repercussions of rapid urbanization; and through popular culture and shifting social relations. The book will be of interest not only to the specialist in urban studies but also to the general reader with an interest in Dar es Salaam's environmental, social and cultural history. James Brennan is a Lecturer in History at the School of Oriental & African Studies (SOAS), University of London. His research interests include nationalism and urbanization in Tanzania, and he is currently researching the historical role of radio and other mass media in East Africa's political culture. Andrew Burton is an Honorary Research Fellow of the British Institute in Eastern Africa, based in Addis Ababa. He has published widely on East African urban culture; and his current interests are the history of youth, urbanization and delinquency in Eastern Africa. Yusuf Lawi is the former Head of the Department of History at the University of Dar es Salaam; and is currently Senior Lecturer in History and Deputy Director of the University's Centre for Continuing Education. He specializes in environmental and social history.
Includes bibliographical references and index.
Keywords: Brennan, James R